THE SPILL-OVER EFFECTS OF FAMILY RELATIONSHIP AND SOCIOECONOMIC STATUS ON CHILDREN BEHAVIOURAL REACTIVITY - Olusegum Emanuel Afolabi (European Scientific Journal, ESJ, 2013)
Numerous studies have come up with an assumption that children nurtured in a conflict, dysfunctional and diverse family contexts show inconsistent forms of domino effect that transverse various developmental domains. A mountain of evidence also established that different family factors such as: parents respond to child’s distress, family emotional environment, family income and inter-maternal effectiveness explained children’s behavioural socialization. This paper has, therefore, sought to assess and analyse empirical research literature on the relative spill-over effects of the quality of couple’s relationship and socioeconomic status (SES) on a child’s behavioural functioning. The paper employs and reviewed empirical literature that assess and supports the associations between family relation, SES and child’s behavioural adjustment. Finally, findings revealed that children reared in a poor family background and experienced family instability are probable of developmental psychopathology problems in teenage years.